Brain circuits for the internal monitoring of movements - Sommer, Marc A. (2008)
Each of our movements causes spurious sensations that must be discriminated from the inputs that really matter – those representing our environment. Here we consider circuits for dealing with this problem in the primate brain. Such circuits convey a copy of each motor command, known as a corollary discharge (CD), to brain regions that use sensory input. In the visual system, CD signals have been hypothesized to produce a stable visual percept from the jumpy images resulting from our rapid eye movements. A candidate pathway for providing CD for vision ascends from the superior colliculus to the frontal cortex in the primate brain. This circuit conveys warning signals about impending eye movements that are used for planning subsequent movements and analyzing the visual world. Identifying this circuit has provided a model for studying CD in other primate sensory systems and may lead to a better understanding of motor and mental disorders.